Perfil clínico e sobrevida de pacientes acometidos pelo Linfoma de Hodgkin clássico: um estudo retrospectivo - Rabelo, Diogo Henrique (2022)
Hodgkin lymphoma (HL) has a unique cellular composition, represented by neoplastic cells known as Hodgkin and Reed Sternberg cells (HRS), which are arranged in an inflammatory background. HL is considered one of the most frequent neoplasms in young adult populations. Classical Hodgkin's Lymphoma (cHL) accounts for approximately 90% of all HL cases. The treatment of this lymphoma is carried out with cycles of chemotherapy and/or radiotherapy, depending on the clinical characteristics of the patient and the disease. Therefore, the objective of the present study was to analyze the sociodemographic and clinical profile of patients affected by cHL and treated in the Oncology sector of the Hospital de Clínicas da Universidade Federal de Uberlândia (HC-UFU), and to verify the association with survival, response therapy and we, we are. This study includes two hundred and forty-six (246) patients diagnosed with cHL treated at the Oncology sector of the HC-UFU from January 2003 to January 2021. The associations between the variables were created through tests of integrated solutions of single and multiple risks and the dimensions that survived were created through the Meier curvature and the model of proportional measures of Cox. Of the 246 patients, 139 (56.5%) were male and the mean age found was 35 years. It was observed that hypertensive patients were 6.2 times (OR: 6.191; p<0.001) more likely to die, whereas those with extra lymph node involvement were 4.6 times (OR: 4.62; p=0.008) more chances of dying. Bleomycin was presented as a protective factor (OR: 0.321; p=0.049) for the relapse outcome. On the other hand, the presence of type II diabetes mellitus was a predictive factor for the patient not having complete remission of the lymphoma (OR: 0.112; p=0.007) and extranodal involvement was presented as a predictive factor of recurrence (OR: 5.615; p=0.002). Mean overall (OS) and disease-free survival (DFS) of 69.3% and 52.8%, respectively, were observed, with the histological subtype of cHL, patients with systemic arterial hypertension, therapeutic regimen and lymphoma recurrence, the variables that had significant associations. with the survivors. In this, the results of the study showed a positive impact on the identification of patient characteristics, disease behavior and the establishment of the disease as variables with mortality, complete remission between the factors that influence OS and DFS, which may contribute to the association in the identification of prognostic and treatment characteristics of patients with cHL treated at the institution.